Pengembangan e-Book IPA Model PjBL untuk Meningkatan Keterampilan Berpikir Kreatif Peserta Didik SMP - Unika Setyani; Ichwan Restu Nugroho; Jumadi Jumadi; Suyanta Suyanta; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to develop a science e-book with material on the respiratory system using the PjBL model which can be used to improve students' creative thinking skills. This is a R&D using Borg and Gall research design. This research uses a one group pretest-posttest design. Subjects were 31 students in grade 8C of SMP Negeri 5 Depok Yogyakarta. Level of product suitability show that in terms of content suitability, presentation suitability and language suitability, as well as the characteristics of PjBL e-books, the average value is 3.25 in the very good category. Graphic aspects as well as technical quality and usability aspects received an average score of 3.40 in the very good category, meaning this e-book can be used in learning at school. Furthermore, the average product practicality level results for students were 90.10% in the very practical category. The research results show that the PjBL model science e-book can improve students' creative thinking skills with a normalized gain test of 0.7 in the high category. Therefore, the e-book with material on the respiratory system that has been developed can facilitate the application of the PjBL model and improve students' creative thinking skills.